3,(2):2,9+1,1(4):(-10,3)
Răspunsuri la întrebare
Răspuns de
4
Răspuns:
- 1
Explicație pas cu pas:
3,(2) = (32-3)/9 = 29/9
2,9 = 29/10
1,1(4) = (114-11)/90= 103/90
10,3 = 103/10
3,(2) : 2,9 + 1,1(4) : (-10,3) =
29/9 : 29/10 + 103/90 : (-103/10) =
29/9 x 10/29 + 103/90 x (-10/103) =
10/9 + ( - 1/9) =
10/9 - 1/9 =
9/9 =
1
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă